2007
DOI: 10.1583/07-2147.1
|View full text |Cite
|
Sign up to set email alerts
|

Cryoplasty Therapy for Limb Salvage in Patients With Critical Limb Ischemia

Abstract: Cryoplasty therapy is a safe and effective method of treating infrapopliteal disease, providing excellent acute outcomes and a high rate of limb salvage in patients with CLI. Study outcomes support the use of cryoplasty therapy as a primary treatment option for patients with CLI secondary to below- knee disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
0
25
0
2
Order By: Relevance
“…Ancak arteriyel yapılarda kronik uzun segment tıkanıklık, yaygın kalsifikasyon, birden çok seviye tutulumu olması perkütan endovasküler işlem başarısını düşürmektedir (24). Son dönemlerde aterektomi, kriyoplasti, kesici balonlar ve lazer anjiyoplastinin diz altı arterlerde güvenle uygulanabileceği gösterilmesine rağmen bu uygulamaların konvansiyonel yöntemlere üstünlüğü olmadığı ve konvansiyonel yöntemlerden daha maliyetli yöntemler olduğu saptanmıştır (25)(26)(27)(28). Yine son yıllarda perkütan işlemlerde ilaç salınımlı balonların etkili olabileceği düşünülmüş ancak bunların konvansiyonel balonlara belirgin üstünlüğü olmadığı çeşitli çalışmalarla gösterilmiştir (29,30).…”
Section: Discussionunclassified
“…Ancak arteriyel yapılarda kronik uzun segment tıkanıklık, yaygın kalsifikasyon, birden çok seviye tutulumu olması perkütan endovasküler işlem başarısını düşürmektedir (24). Son dönemlerde aterektomi, kriyoplasti, kesici balonlar ve lazer anjiyoplastinin diz altı arterlerde güvenle uygulanabileceği gösterilmesine rağmen bu uygulamaların konvansiyonel yöntemlere üstünlüğü olmadığı ve konvansiyonel yöntemlerden daha maliyetli yöntemler olduğu saptanmıştır (25)(26)(27)(28). Yine son yıllarda perkütan işlemlerde ilaç salınımlı balonların etkili olabileceği düşünülmüş ancak bunların konvansiyonel balonlara belirgin üstünlüğü olmadığı çeşitli çalışmalarla gösterilmiştir (29,30).…”
Section: Discussionunclassified
“…Second, we treated very complex lesions in this study compared to most previous studies, which treated mainly Trans Atlantic Inter-Societal Consensus (TASC) A and B lesions. 3,[6][7][8][9] This is emphasized by the mean length of our lesions being 15 cm. Bakken et al 10 also have shown poor initial technical success of 78% with cryoplasty in more challenging lesions.…”
Section: Discussionmentioning
confidence: 59%
“…Third, the majority of lesions treated with cryoplasty in our study were reinterventions compared to previous studies in which all were de novo lesions. [3][4][5][6][7] Interestingly, some of our initial cryoplasty failures responded to balloon angioplasty. This may indicate that some lesions require a higher inflation pressure, which cannot be delivered via cryoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several adjunctive endovascular devices, including atherectomy, cryoplasty, cutting balloons, and laser, have been shown to be feasible and safe in the infrapopliteal vessels but have failed to show superior efficacy when compared to conventional, less expensive therapies. 45,[63][64][65] These devices add cost to the basic endovascular procedure, and therefore their added expense needs to be justified. 66) The data suffer from many of the limitations of the observational surgical series in that they largely represent the retrospective reports or uncontrolled registries, subject to selection bias, at individual centers.…”
Section: New Technologiesmentioning
confidence: 99%